Learning Perspectives of Publication - Joel Rey U Acob (The Journal of Palembang Nursing Studies, 2022)
The growing demand of scientific-driven results to strengthen nursing profession, researchers should consistently engage in executing knowledge-generating actions. Disseminating research results either through fora or in printed publication deepens understanding on issues particularly on caring and nursing education. But will research endures its aim of offering relevant evidence during pandemic era where conventional data collection strategies are less feasible, hence this viewpoint.